Pharmaceutical Approval Update - Choy, Mary (P T, 2017)
Abuse-deterrent hydrocodone bitartrate (Vantrela ER) for long-term opioid treatment; etelcalcetide (Parsabiv) for secondary hyperparathyroidism in patients with chronic kidney disease on hemodialysis; and deflazacort (Emflaza) for Duchenne muscular dystrophy